(untitled) (IASH Indian Journal of Arid Horticulture, 2025)
The research findings indicated that diverse combinations of biodynamic, silica and Dashparni have remarkable influence on the growth and yield characteristics of the tomato Ajeet variety cultivated under protected conditions. From a range of treatments and combinations of treatments, treatment T10 (BD 500 @7 5g/ha + BD 501 @ 2.5g/ha + Silica @ 1% + Dashparni @10%) produced the highest plant height at 30 DAT, 60 DAT and at final harvest (44.23, 88.56 and 244.90 cm, respectively), leaf area (254.8 cm2), minimum day to flowering (42.66) and least day to harvest (89.00%), maximum number of branches (25). The maximum fruit length of 6.66 cm, maximum fruit diameter of 5.20 cm, maximum fruit volume of 115.33 cc, maximum fruit weight of 109.26 g, number of fruits per plant (46.46), yield per plant of 5.05 kg, yield per square metre of 11.23 kg and yield per acre of 44.94 t were attained in T10 (BD 500 @ 75 g/ha + BD 501 @ 2.5 g/ha + Silica @ 1% + Dashparni @ 10%) compared to the control.